Genetic Profiling Reveals High Allelic Diversity, Heterozygosity and Antigenic Diversity in the Clinical Isolates of the Theileria annulata From India - Roy, Sonti; Bhandari, Vasundhra; Dandasena, Debabrata; Murthy, Shweta; Sharma, Paresh (Frontiers in Physiology, 2019)
Tropical theileriosis caused by Theileria annulata infection is a significant livestock disease affecting animal health and productivity resulting in substantial monetary losses worldwide. Despite the use of an effective vaccine for disease control still, a high incidence of infection is reported from India. One of the many reasons behind the ineffective disease control can be the existence of genetically diverse Theileria annulata parasite population in India. Therefore, studies focusing on understanding the genotypes are warranted. In this study, we have performed a genetic analysis of the Indian T. annulata field cell lines and the vaccine line using microsatellite markers, Genotyping based sequencing (GBS) and tams1 gene polymorphism. The degree of allelic diversity and multiplicity of the infection was determined to be high in the Indian population. No geographical sub-structuring and linkage disequilibrium were observed in the population. High population diversity was found which were similar with countries like Oman, Tunisia and Turkey in contrast to Portugal and China. The presence of multiple genotypes as determined by microsatellite marker genotyping, GBS analysis and tams1 gene polymorphism point towards a panmictic parasite population in India. These findings are the first report from India which would help in understanding the evolution and diversity of the T. annulata population in the country and can help in designing strategies to effectively control the disease.